Pembuatan Website Virtual Reality Tour Sebagai Media Promosi Tempat Wisata Danau Ngebel Kabupaten Ponorogo - Setyawan, Dimas Ari; Utomo, Prasetyo Yekti; Isa, Muhammad; Aji, Mochamat Bayu; Agasta, Rio; Putra, Septian Dwi Maulana (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Virtual reality tour is a platform that allows users to visit locations online in real time through 360-degree panoramic images. The technology known as virtual e-tour gives users the impression that they are part of the scenery and makes it easy to see, capture, and analyze virtual data. Lake Ngebel has extraordinary natural tourism potential, but there are still several problems in its promotion. The main problems include lack of promotion, diversification of tourism products, coordination between stakeholders, and unclear tourism image. To overcome this, an integrated solution is needed such as increasing promotion in various media. This community service applies web-based virtual tour technology to provide information that makes it easier for tourists in Ponogoro regarding the Lake Ngebel tourist attraction and makes it easier for the general public to obtain information on the layout of services. Activities during the community service were carried out in several stages, namely: location survey, photo data collection, website design and finally website socialization. The asset data used in this community service were 11 360 panoramic images, 11 information images, and 1 video of a fountain show. The virtual tour website was created using the 3Sixty application.